Notes on the typification of Angiopteris tamdaoensis and A. tonkinensis (Marattiaceae) - Dong, Shi-Yong; Vasques, Diego Tavares (Phytotaxa, 2023)
In the fern family Marattiaceae, both Angiopteris tamdaoensis (Hayata 1919: 91) Xiang & Wang (2020: 7) and A. tonkinensis (Hayata 1919: 88) Camus (1989: 34) were originally published by Hayata (1919) based on materials from northern Vietnam (Mt. Tamdao) collected in 1917. Stressing the distinctness of fused-sporangia (synangia) in A. tonkinensis, Hayata (1919: 88) even proposed a new genus, Protomarattia, to accommodate this species. Almost since the publication, the controversy has arisen on the identity of A. tamdaoensis and A. tonkinensis among pteridologists. Christensen and Tardieu-Blot (1935) and Ching (1958a, 1958b) synonymized A. tonkinensis and A. tamdaoensis, while Pichi Sermolli (1968) argued A. tonkinensis is a distinct species representing a good genus. Camus (1989) accepted A. tonkinensis as a good species while treated A. tamdaoensis as a synonym of A. somae (Hayata 1915: 256) Makino & Nemoto (1925: 1563), which was based on the observation that the fusion of sporangia exhibits a series of graded intermediates in Archangiopteris Christ & Giesenhagen (1899: 72) and Protomarattia, and also occurs to some extent in Angiopteris sensu Hoffmann (1796: 29) (Hill & Camus 1986). Recently, Wang et al. (2020) proposed both A. tamdaoensis and A. tonkinensis are good species, insisting the latter being distinguishable from the former by the marginal synangia. We noticed that the A. tonkinensis reported by various authors (e.g., Ching 1958a; Ching et al. 1964; Dong 2004; He et al. 2013) from Hainan was corrected to be A. tamdaoensis by Wang et al. (2020).